Rationale, design, and methods for Canadian alliance for healthy hearts and minds cohort study (CAHHM) – a Pan Canadian cohort study. (December 2016) - Anand, Sonia; Tu, Jack; Awadalla, Philip; Black, Sandra; Boileau, Catherine; Busseuil, David; Desai, Dipika; Després, Jean-Pierre; de Souza, Russell; Dummer, Trevor; Jacquemont, Sébastien; Knoppers, Bartha; et al.
Abstract Background The Canadian Alliance for Healthy Hearts and Minds (CAHHM) is a pan-Canadian, prospective, multi-ethnic cohort study being conducted in Canada. The overarching objective of the CAHHM is to understand the association of socio-environmental and contextual factors (such as societal structure, activity, nutrition, social and tobacco environments, and access to health services) with cardiovascular risk factors, subclinical vascular disease, and cardiovascular and other chronic disease outcomes. Methods/Design Participants between 35 and 69 years of age are being recruited from existing cohorts and a new First Nations Cohort to undergo a detailed assessment of health behaviours (including diet and physical activity), cognitive function, assessment of their local home and workplace environments, and their health services access and utilization. Physical measures including weight, height, waist/hip circumference, body fat percentage, and blood pressure are collected. In addition, eligible participants undergo magnetic resonance imaging (MRI) of the brain, heart, carotid artery and abdomen to detect early subclinical vascular disease and ectopic fat deposition. Discussion CAHHM is a prospective cohort study designed to investigate the impact of community level factors, individual health behaviours, and access to health services, on cognitive function, subclinical vascular disease, fat distribution, and the development of chronic diseases among adults living in Canada.